Effect of BALANCE Evaluation and Training System on Early Trunk Control Ability of Patients with Cerebral Apoplexy - Wei YANG; Hong WANG; Yangfan XU; Zhiwei MU; Rongliang HU; Zhuoming CHEN (康复学报)
Objective:To investigate the curative effect of BALANCE evaluation and training system in improving early trunk control ability of stroke patients.Methods:A total of 40 stroke patients were randomly assigned to the treatment group and the control group, 20 patients in each group. Both groups received neurotrophic and vasoactive drug therapy and conventional Brunnstrom, NDT of Bobath, Rood, PNF, MRP and trunk muscle strength control training, etc.. Furthermore, the treatment group also applied the BALANCE evaluation and training system to train their trunk control ability. The treatment was carried out six days a week for four weeks. The trunk control test (TCT), Postural assessment scale for stroke patients (PASS) and the BALANCE evaluation system for assessing the envelope area and Linear length of locus (LNG) in seat position were applied for both groups before and after training.Results:There was no significant difference between the two groups in the scores of TCT scores, PASS scores, envelope area and LNG before training (P>0.05). TCT scores and PASS scores in the treatment group were increased significantly, and the envelope area and LNG were decreased significantly (P<0.01 or P<0.05) after training, there were significant differences between the two groups in the scores of TCT scores, PASS scores, envelope area and LNG after training (P<0.05).Conclusion:The BALANCE evaluation and training system could effectively improve stroke patients'early trunk control ability.